2021
DOI: 10.3390/cancers13071612
|View full text |Cite|
|
Sign up to set email alerts
|

Somatic Mutation Profiling in the Liquid Biopsy and Clinical Analysis of Hereditary and Familial Pancreatic Cancer Cases Reveals KRAS Negativity and a Longer Overall Survival

Abstract: Pancreatic ductal adenocarcinoma (PDAC) presents many challenges in the clinic and there are many areas for improvement in diagnostics and patient management. The five-year survival rate is around 7.2% as the majority of patients present with advanced disease at diagnosis that is treatment resistant. Approximately 10–15% of PDAC cases have a hereditary basis or Familial Pancreatic Cancer (FPC). Here we demonstrate the use of circulating free DNA (cfDNA) in plasma as a prognostic biomarker in PDAC. The levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Pancreatic ductal adenocarcinoma (PDAC) is known for its resistance to traditional therapy, with a high percentage of recurrence and a poor five-year survival rate [ 1 ]. Recently, several reports revealed that PDAC are more vulnerable to ferroptosis inducers [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic ductal adenocarcinoma (PDAC) is known for its resistance to traditional therapy, with a high percentage of recurrence and a poor five-year survival rate [ 1 ]. Recently, several reports revealed that PDAC are more vulnerable to ferroptosis inducers [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors wish to make the following corrections to this paper [1]: In the published version, Figure 4 appeared as a duplication of Figure 1b. Furthermore, the legend of Figure 2 has been corrected to accurately reflect the data shown.…”
mentioning
confidence: 99%